Infinite hope : how wrongful conviction, solitary confinement, and 12 years on death row failed to kill my soul - Graves, Anthony, 1965- (Beacon Press, 2018)
"Written by a wrongfully convicted man who spent 16 years on death row and 12 years in solitary confinement, a powerful memoir about fighting for--and winning--exoneration. Infinite Hope is an argument against the death penalty through one man's personal story. It is about a man enduring a life on death row year after year, when he knows that he is one hundred percent innocent and that his exoneration is unlikely. Anthony Graves' unbelievable saga started in 1992 when, at 26 years old, he was arrested for killing six people in Somerville, Texas. Despite his air-tight alibi, his unwavering insistence that he had no knowledge of the crime, and a lack of physical evidence linking him to the scene, Graves was arrested, charged with capital murder, and eventually sentenced to death. He spent nearly two decades defending his innocence from behind bars. With the help of a hard-charging journalist, Graves' story of injustice and the astounding malfeasance he encountered at every turn was published in Texas Monthly. In 2011, eighteen years after his nightmare began, Graves was finally exonerated. The prosecutor in his case was later disbarred. Poignant and skillfully wrought, Graves writes about fighting for his dignity, trying to maintain his sanity, the excruciating reality of being innocent behind bars, and how he endured one setback after another as he and his lawyers chipped away at the state's case against him. Infinite Hope exposes an extreme version of when the judicial system is wrong and, as Graves describes it, "what people go through when they're treated as disposable.""--Provided by publisher.